DIRETRIZES DE INFRAESTRUTURA E EQUIPAMENTOS PARA IMPLANTAÇÃO DE BANCO DE LEITE HUMANO REGIONAL EM HOSPITAL PÚBLICO DA REGIÃO CENTRAL DO ESTADO DO RIO GRANDE DO SUL - Costa, Ivone Adriana Garcia (2024)
Human milk banks (HMB) are essential for the promotion and support of breastfeeding (BF), as they play a critical role in the collection, processing, and distribution of human milk (HM) for premature or low-birth-weight newborns who cannot be breastfed by their own mothers. In addition to being a strategic component of public policies aimed at maternal and child health, HMBs have significant potential for national expansion and strengthening. This study aimed to investigate scientific evidence on the status of HMBs in Brazil through an integrative review and to develop technical guidelines for designing, building, and implementing a regional HMB in a large hospital in the interior of Rio Grande do Sul. The research was conducted in the LILACS database using the DeCS descriptors "Human Milk Banks," "Breastfeeding," and "Child Health." The process included the formulation of a guiding question, literature search, critical data analysis, and study selection based on inclusion and exclusion criteria. Of the 22 studies identified, 8 were selected: 3 quantitative, 2 cross-sectional, 1 qualitative, 1 reflective, and 1 systematic review. The evidence highlighted the historical development of HMBs, the benefits of BF for mothers and infants, the importance of donor profiles, and strategies to increase milk donations, as well as challenges related to multidisciplinary collaboration and the efficient operation of these banks. The findings also demonstrated that well-planned and sustained initiatives can positively impact maternal and child health by promoting higher quality and more humanized care. Based on this analysis, technical guidelines were developed focusing on the infrastructure and operational flows of a regional HMB, emphasizing replicable and sustainable interventions. These guidelines include an assessment of environmental conditions, the establishment of criteria for HMB operations, and strategies to improve BF indicators. The resulting technical product is characterized by its strategic vision and potential to promote short- and medium-term social transformations, benefiting not only the women and children served but also contributing to reducing regional health inequalities. It is concluded that the continuous improvement of HMBs, combined with the development of integrated public policies, is essential to ensure the right to BF and expand assistance to premature and low-birth-weight newborns. The implementation of a regional HMB, based on the proposed guidelines, can support care actions for women and children, enhancing the quality of assistance and the sustainability of breastfeeding practices in Brazil.